Responsabilidad penal empresarial: antecedentes y aproximación a la legislación en Colombia - Ardila Torres, Adrián Danilo (Derecho penal y criminología, 2023)
The results of the studies carried out on criminal policy have shown the need to carry out real legislative reforms at the internal level and in terms of international cooperation in order to counteract the negative impact that the risks derived from the creation of companies have been showing in criminal matters that use their economic power to violate collective property and of interest to the States. The administrative sanctioning law has proven ineffective in the face of the challenges proposed by these legal entities, who have used the different forms of association to offer a “facade” of legality and perpetrate deviant conduct within society. For this reason, it is reasonable to make enormous efforts to use the ductility of the law and harmonize it with social reality, implementing for this purpose its own criminal imputation system for legal or business persons.